Combustion of ultrafine aluminum in air - Ilyin A. P. Aleksandr Petrovich; Gromov A. A. Aleksandr Aleksandrovich; Vereshchagin (Vereschagin, Vereshagin) V. I. Vladimir Ivanovich; Popenko E. M.; Surgin V. A.; Lehn Y. (2001, 2001)
Title screen